External Factors Affect English Learning in Rural Elementary Schools: A Qualitative Study - Mufidah Nur Aliyyah Yusuf; Yuli Astutik; Fika Megawati (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2023)
The aim of this study was to discover some external factors that influence the difficulties of teaching and learning English in rural schools for young learners. To obtain detailed data or information, data was collected in this study through observation and interviews using a qualitative research method and a type of case study. The research was conducted at an Al Fatch elementary school in the Silo sub-district of Jember Regency, East Java. The findings revealed that several external factors influence the difficulty of teaching and learning English for young students in rural schools, including 1) the school's location is far from urban areas, making it difficult for the community to reach it; 2) inadequate school infrastructure; 3) inadequate school facilities cannot support the continuity of the English teaching and learning process; 4) a lack of learning resources for students and teachers; 5) the language barrier, which is influenced by the community surrounding the school, which speaks the local language more frequently, makes it difficult for students to understand Indonesian as a medium of instruction in the teaching process.